Women who love too much when you keep wishing and hoping he'll change - Norwood, Robin (New York Pocket Books, 2008)
Why do so many women become obsessed with the wrong men -- men who are emotionally unavailable, addicted to work, alcohol, or other women -- men who cannot love them back? Robin Norwood helps these women recognize, understand, and change the way they love through a series of intimate, revealing case histories
1
Keywords: Relationship addiction; Women -- Psychology